2008
DOI: 10.1103/physrevb.78.180413
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evidence for unstable magnons at high fields in the Heisenberg antiferromagnet on the square lattice

Abstract: We find evidence for decaying magnons at strong magnetic field in the square lattice spin-1/2 Heisenberg antiferromagnet. The results are obtained using quantum Monte Carlo simulations combined with a Bayesian inference technique to obtain dynamics and are consistent with predictions from spin-wave theory.The square lattice spin-1/2 Heisenberg antiferromagnet ͑2DHAF͒ is the archetype quantum antiferromagnet and describes the magnetism of the mother compounds of the high-T c cuprate materials. 1 While the 2DHAF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
101
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(112 citation statements)
references
References 17 publications
11
101
0
Order By: Relevance
“…In this case, magnons were shown to be overdamped in most of the Brillouin zone by both the spin-wave calculation, which used a different version of the SCBA, 16 and by the numerical QMC simulations. 17 Such a difference in the effect of magnon interaction between S = 1/2 and S ≥ 1 models deserves a separate discussion. We compare directly the imaginary part of the magnon self-energy at the quasiparticle pole, −ImΣ k (ǭ k ), for the S = 1/2 case obtained in Ref.…”
Section: Self-consistent Theory Of Magnon Decays a One-magnon Grmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, magnons were shown to be overdamped in most of the Brillouin zone by both the spin-wave calculation, which used a different version of the SCBA, 16 and by the numerical QMC simulations. 17 Such a difference in the effect of magnon interaction between S = 1/2 and S ≥ 1 models deserves a separate discussion. We compare directly the imaginary part of the magnon self-energy at the quasiparticle pole, −ImΣ k (ǭ k ), for the S = 1/2 case obtained in Ref.…”
Section: Self-consistent Theory Of Magnon Decays a One-magnon Grmentioning
confidence: 99%
“…However, this consideration neglects the spectral weight redistribution. The analytical calculation 16 and the QMC study 17 have shown a significant non-Lorentzian broadening of the spectral lines, which takes the form of a double-peak structure in the dynamical susceptibility. Therefore, the overdamping in the S = 1/2 case is produced by two effects: broadening of the quasiparticle peak and spectral weight redistribution.…”
Section: Self-consistent Theory Of Magnon Decays a One-magnon Grmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods have been proposed: the Average Spectrum Method 8 (ASM), which has been recently applied to lattice spin models 9 but also to realistic off-lattice systems 10 , the Stochastic Analytic Continuation (SAC) method 11 and also the spectral analysis described in Ref. 12.…”
Section: Introductionmentioning
confidence: 99%
“…As far as bosonic degrees of freedom are considered, QMC calculations allow static properties, energetics and structure functions, to be computed exactly [1][2][3][4][5][6] even for strongly correlated systems, for which analytic approaches yield only approximate results. Furthermore the possibility of reconstructing dynamical properties of bosonic systems, like excitation spectra and response functions, from imaginary time correlation functions has been explored with remarkable results [3,[7][8][9][10][11][12][13]. On the other hand, for fermionic degrees of freedom the situation is considerably complicated by the well-known sign problem [14,15]: computational cost increases exponentially with the system size.…”
Section: Introductionmentioning
confidence: 99%